Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Kolase - Yurna Devi; Sri Rejeki; Ika Pribianti (Jurnal Pendidikan Tuntas, 2023)
This research aims to improve fine motor skills through collage activities. This research is Classroom Action Research. The research subjects were Group B children with a total of 15 children consisting of 9 boys and 6 girls for the 2020/2021 academic year. The object of this research was fine motor skills. Data collection techniques are carried out using observation and documentation. The tool used is an observation instrument sheet. The data analysis technique was carried out descriptively quantitatively. This research was carried out in two cycles. The results of the research showed that the percentage of achievement in the fine motor skills of Group B children at the Pre-Cycle stage was only 40.09%, increasing in Cycle I to 50.94% and in Cycle II reaching 73.88% in the Developing According to Expectations (BSH) category. Based on the research results, it can be concluded that throughcollage activities, fine motor skills can be improved in children aged 5-6 years at Raudhatul Hasanah Suka Damai Kindergarten, Ujungbatu District, Rokan Hulu Regency. Keywords : Fine motor skills, collage, Classroom action research